Book Review: The Boyne Currach: from Beneath the Shadows of Newgrange By Claidhbh Ó Gibne - Tom Jackson (EXARC Journal)
Claidhbh Ó Gibne has devoted himself to building traditional currachs and researching their history. His new volume, The Boyne Currach: From beneath the shadows of Newgrange, puts the currach in the context of the history of hide-covered boats, explains in detail how to build one, and describes the current experimental construction of a very large example.